Old Mutual Insurance administration system - Mihloro, Mornisher (Midlands State University, 2017)
Old Mutual Insurance System is a fully integrated browser-based insurance system that facilitates for faster interaction between potential clients, insured clients and the organisation. The system was developed with the clients at the heart of system and this provided an end-to-end policy administration system with a client-centric approach. The aim of the Insurance Administration System was to reduce application process and insurance claims approval process and address customer services effectively in a shorter time. The Insurance Administration System allows for clients to apply for insurance policies and claims online and also check their monthly premiums without visiting Old Mutual offices in person. Underwriters can view clients’ documents online and approve their insurance policy applications and their claims applications within a short period of time. Underwriters can also update the clients’ monthly premiums in their respective accounts. The Insurance Administration System was developed using PHP, MySQL and Dreamweaver. To obtain what the end user expected from the Insurance Administration System, the developer used interviews, questionnaires, joint application development and observation. The Insurance Administration System reduced costs, improved efficiency and enhanced controlled user access and authority limits. In the past, the insurance company had to manually maintain each customer records and this required a lot of man power and the amount of time spent after creating each record and updating them was huge. The introduction of the Insurance Administration System made it possible to manage all records with ease, eliminating errors in the process.